Telesite: monitoramento e gerência de estações remotas de TV e Telecom - Piska, Cláudio Marcelo (2018)
This work aims to develop a telemetry solution with configurable parameters, capable of remotely monitoring a television or telecommunications relay station. This need arose from the technical perception in the field, where failures are usually detected when it is no longer possible to avoid the loss of quality of service or even affect its availability. In addition, it is often not possible to determine what exactly occurred. With these needs, a reasonably simple and low-cost solution based on the Raspberry Pi development board has been found, which has many features that enable it to capture sensor data, treat it, and make interactions with central management, all of which using free software. With this telemetry system, it is sought to have real-time information of a remote station's operation, prevention, failure information, data analysis, important items for more assertive decision making. The product can be an important tool to help reduce high costs with displacements of technical labor and equipment exchange.